2000
DOI: 10.1042/bst0280208
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G in the human placenta: expression and potential functions

Abstract: HLA-G is a non-classical class I molecule specifically expressed in the placenta, suggesting that it might have a physiological function at the materno-foetal interface. The structural characteristics of HLA-G, the placental pattern of expression and the functional properties of this class Ib glycoprotein in vitro are described and evaluated in the context of pregnancy. The possible anti-viral function of HLA-G, its modulatory role of natural killer cell activity and its likely non-immunological functions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 10 publications
1
20
0
3
Order By: Relevance
“…2G) and not in the trophoblasts within the decidua that had stained positively for both CK-7 and Cdx-2 in serial sections (data not shown). This result agrees well with published work that reports strong expression of the sHLA-G at the fetal-maternal interface (Le Bouteiller et al, 1999), where it has been suggested to contribute to the elimination of potentially harmful maternal cytotoxic allogenic T cells during pregnancy (Le Bouteiller, 2000). This result suggests that the EVTs may stop secreting sHLA-G as they enter the decidua and that HLA-G expression may be restricted to the cellassociated membrane form found on InEVTs and EnEVTs in vivo .…”
Section: Dunk Et Alsupporting
confidence: 83%
“…2G) and not in the trophoblasts within the decidua that had stained positively for both CK-7 and Cdx-2 in serial sections (data not shown). This result agrees well with published work that reports strong expression of the sHLA-G at the fetal-maternal interface (Le Bouteiller et al, 1999), where it has been suggested to contribute to the elimination of potentially harmful maternal cytotoxic allogenic T cells during pregnancy (Le Bouteiller, 2000). This result suggests that the EVTs may stop secreting sHLA-G as they enter the decidua and that HLA-G expression may be restricted to the cellassociated membrane form found on InEVTs and EnEVTs in vivo .…”
Section: Dunk Et Alsupporting
confidence: 83%
“…HLA-G may (39) or may not (40) be expressed in the human preimplantation embryo; however, the immediate postimplantation stages of development are not available for evaluation with human pregnancy. The pattern of Mamu-AG expression predominantly in cytotrophoblasts invading the maternal vessels and endometrium strongly resembles the localization of HLA-G in the human placenta at 6-12 weeks of gestation, where HLA-G expression is restricted to cytotrophoblasts that have differentiated along the invasive pathway (5,6,8). Trophoblast invasion into the arterial wall, accompanied by displacement of the endothelial basement membrane and loss of smooth muscle cells (27,41), limits the contractile capacity of endometrial arteries and permits a substantial and constant blood flow to the placenta and fetus.…”
Section: Discussionmentioning
confidence: 99%
“…shown to be expressed on the surface of invasive extravillous trophoblasts of the human placenta, with potential significance for regulation of the maternal immune response to pregnancy (1)(2)(3)(4)(5)(6). As with other MHC class I molecules, HLA-G is expressed on the cell surface complexed with ␤ 2 -microglobulin and interacts with a variety of receptors on cells of the innate immune system, including NK cells and monocytes (7)(8)(9)(10)(11).…”
Section: T He Nonclassical Mhc Class I Molecule Hla-g Has Beenmentioning
confidence: 99%
“…The membrane was washed twice with TBS and blocked with a 0.2% nonfat dry milk/TBS solution overnight at 4°C. Following blocking, the membrane was washed three times with a 0.1% 4 Abbreviations used in this paper: ISH, in situ hybridization; HA, hemagglutinin. The six nucleotides at the 3Ј terminus (GTAAAG) are derived from intron 4 of Mamu-AG (GenBank accession no.…”
Section: Recombinant Mamu-ag5 Expression and Western Blottingmentioning
confidence: 99%